PENGARUH KEJELASAN SASARAN ANGGARAN, KOMPETENSI, DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA PADA KANTOR DESA SE- KECAMATAN BLAHBATUH, KABUPATEN GIANYAR - Ni Wayan Krisna Purnama Dewi; Ni Wayan Alit Erlinawati (UNHI Press, 2020)
Thisl study aims to determine thel effect of clarityl of budget targets, competencies, andl communityl participationl on village fund managementl accountabilityl inl Blahbatuhl District, Gianyarl Regency. Thel populationl inl thisl study were all village apparatuses inl Blahbatuhl District with 161 apparatus. Thel sample inl thisl study was 9 villages inl Blahbatuhl District with 81 respondents. Thel method of determiningl thel sample usingl purposive sampling, datal were collected usingl a questionnaire that was measured with a Likert scale. Datal were analyzed with Multiple Linear Regression Analysis. based on thel results of thisl study indicate that thel clarityl of budget targets, competencies, andl communityl participationl has a positive andl significant effect on thel accountabilityl of village fund management. Thisl shows that thel better thel clarityl of budget targets, competenciesl andl communityl participation, thel accountabilityl of village fund managementl inl Blahbatuhl District, Gianyarl Regency will be better.